Manufacturing Process Volume 1 - Abd Rahman, Ammar; Subramonian, Sivarao; Minhat, Mohamad; Abd. Rahman, Md. Nizam; Salleh, Mohd Rizal (Penerbit Universiti UTeM, 2013)
Teaching and Learning Series. Faculty of Manufacturing Engineering. Module 8.